Technical training of highly skilled acrobatic girls - Rikhsibayeva, Madina; Rakhmonova, Kamola (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
In this article, a fully developed training program, which includes a set of exercises for the development of strength, coordination, elasticity and speed-strength capabilities of highly qualified acrobatics, will be used to achieve a positive result from basic technical training for acrobatic exercises, which is fully supported